Fraude corporativo: cómo la gobernanza y la auditoría pueden prevenir la manipulación financiera y la quiebra fraudulenta - Palacin, Guido Adrián (2025)
In a globalized economy, financial stability is crucial. Bankruptcy prediction models, like Lensberg et al. (2006), are essential for identifying insolvency risks. However, manipulative financial practices, such as window dressing can distort these predictions by temporarily altering financial statements to hide real problems. This study explores how such manipulations affect the accuracy of these models and examines the integration of criminological indicators for better fraud detection. It also highlights the role of corporate governance and internal culture in preventing fraud, stressing the involvement of stakeholders—particularly employees and auditors—in fostering transparency. While auditors, both internal and external, act as key deterrents to fraud, their ability to predict fraudulent actions is limited. Combining strong corporate governance, active stakeholder participation, and comprehensive auditing can mitigate risks and maintain the integrity of financial information, ultimately ensuring trust in the financial system.